The effect of reporting incentives on International Financial Reporting Standards compliance by unlisted companies in South Africa: using qualitative and quantitative methods - Loliwe, Thando (Department of Finance and Tax, 2019)
This dissertation investigates the factors which influence unlisted companies’ compliance with International Financial Reporting Standards (IFRS) in South Africa at three levels: the global level, the country level, and the company level. This dissertation also considers whether taking such factors into account in the standard-setting process would lead to improved IFRS compliance. This dissertation applies a multiple case study method followed by a national wide survey. Thus, the data were collected by reading the IFRS, and through questionnaires and interviews. A total of 41 companies responded to the survey while five (5) companies participated in the case study. This dissertation’s main findings show that at company level, governance and financial people working for these companies are significant factors which influence their IFRS compliance. Further, non-auditing and/or non-accounting companies are highly reliant on their external auditors in order to comply with the IFRS. The findings also show that at country level, economic, legal, cultural and professional factors influence these companies’ IFRS compliance. At global level, the findings show that the international recognition of IFRS, transparency, comparability, understandability, foreign operations, and importing and exporting are the factors which influence these companies’ IFRS compliance. There are several contributions that can be attributed to this dissertation. First, this dissertation contributes to the literature by extending the research regarding factors (or some indicators for factors) which influence unlisted companies’ IFRS compliance and these companies’ experience of using IFRS in South Africa. Further, this dissertation suggests a model which explains those indicators which appear to influence unlisted companies’ IFRS use at company level. Second, this dissertation contributes to the literature by testing five theories (these are, decision usefulness theory, agency theory, stewardship theory, stakeholder theory and institutional theory) on unlisted companies. Third, this dissertation’s original contribution is to use a self-prophecy effect to gain a better understanding of unlisted companies’ predicted continuing use of IFRS.